2021
DOI: 10.1073/pnas.2114828118
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 exposure in wild white-tailed deer ( Odocoileus virginianus )

Abstract: Widespread human SARS-CoV-2 infections combined with human–wildlife interactions create the potential for reverse zoonosis from humans to wildlife. We targeted white-tailed deer (Odocoileus virginianus) for serosurveillance based on evidence these deer have angiotensin-converting enzyme 2 receptors with high affinity for SARS-CoV-2, are permissive to infection, exhibit sustained viral shedding, can transmit to conspecifics, exhibit social behavior, and can be abundant near urban centers. We evaluated 624 prepa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
193
3
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(226 citation statements)
references
References 24 publications
1
193
3
3
Order By: Relevance
“…Recently, white-tailed deer fawns were demonstrated to be susceptible to experimental SARS-CoV-2 infection [ 20 ]. Also, it was recently reported that sero-surveillance studies conducted in 2021 show that 40% of wild white-tailed deer tested across the midwestern US were positive for SARS-CoV-2 neutralizing antibodies [ 21 ]. Although it is unclear at the time of writing if these results are caused by SARS-CoV-2 exposure or cross-reactivity of a yet unidentified closely related coronavirus infection in deer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, white-tailed deer fawns were demonstrated to be susceptible to experimental SARS-CoV-2 infection [ 20 ]. Also, it was recently reported that sero-surveillance studies conducted in 2021 show that 40% of wild white-tailed deer tested across the midwestern US were positive for SARS-CoV-2 neutralizing antibodies [ 21 ]. Although it is unclear at the time of writing if these results are caused by SARS-CoV-2 exposure or cross-reactivity of a yet unidentified closely related coronavirus infection in deer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was recently reported that sero-surveillance studies conducted in 2021 show that 40% of wild white-tailed deer tested across the midwestern US were positive for SARS-CoV-2 neutralizing antibodies [ 21 ]. Although it is unclear at the time of writing if these results are caused by SARS-CoV-2 exposure or cross-reactivity of a yet unidentified closely related coronavirus infection in deer [ 21 ]. Surprisingly, antibodies were detected in one sample as early as 2019, and several samples from January to March of 2020 in this serosurvey, but not in sera collected in years prior to 2019 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike our cat samples, the two seropositive deer could represent transmission of SARS-CoV-2 into the local deer population because these samples were collected post pandemic. Interestingly, a recent report showed that 33% of white-tailed deer from 4 states (Illinois, Michigan, New York, and Pennsylvania) were positive for SARS-CoV-2 antibodies [68]. Seropositive animals were only observed from 2019 onward, with pre-pandemic deer testing negative on their SARS-CoV-2 neutralization assay.…”
Section: Discussionmentioning
confidence: 99%